As relações dialógicas no horário gratuito de propaganda eleitoral de Dilma Rousseff em 2014 - Bartolomeu, Talita Cristina (2016)
In this study, we aimed at identifying how the dialogic relations occur in the building of Dilma Rousseff’s election propaganda of 2014, exhibited by the Brazilian election propaganda program, in which she was running for her reelection for the presidence of Brazil. In the proposed investigation, based on Mikhail Bakhtin’s studies, we aimed at (i) verifying the meaning effects raised in the building of Dilma’s propaganda; (ii) which discourses and which answers cross-connect with each other in the produced utterances; (iii) which ideologies they carry to attempt to convince and reach out to the electors, with the objective of acquiring their support by means of votes. In order to do so, we constituted a corpus with six pieces of propaganda – three from the first round and three from the second round – exhibited in the electoral propaganda from August 19th to October 24th of 2014, and we compared the declarative similarities and disparities of both rounds. For the building of our analysis corpus, the television propaganda has been recorded, and all the electoral propaganda has been watched. Next, we selected six pieces of propaganda by sampling, once they all have the same compositional structure. Subsequently, the transcription of all the chosen pieces of propaganda was performed, as well as the analysis of the occurrences. Our analysis repertoire is based, fundamentally, on the qualitative method of bibliographic review, along with the theoretical application to the analyses. By means of the Bakhtinian reflection on dialogism, we showed that the author-person (marketeer) elaborates the declarative content and, as a consequence, interferes with the constitution of the meanings in Dilma’s discourse. In addition, we verified that the discourses disclosed and the dialogues carried out are marked and directed by different social voices in each declarative moment.